(untitled) (Global Journal of Human-Social Science, 2019)
The present study examined the impact of cognitive behavioral group counseling in boosting self-esteem among recidivists. The study was conducted at Sodo and Arba Minch prisons, Ethiopia. This quasi-experimental study used a pre and post-test research design with a control group. During the first stage, the researcher identified recidivists from both prisons. The result revealed that there were 81 and 75 recidivists at Sodo and Arba Minch prisons respectively. All recidivists took the Rosenberg self-esteem scale in order to screen out those who have low self-esteem. Out of these, 21 recidivists of Sodo prison and 24 recidivists of Arba Minch prison were found with low self-esteem. As a result, 21 recidivists of Sodo prison with low self-esteem were assigned into an experimental group and 24 recidivists of Arba Minch prison with low self-esteem were assigned into a control group. Rosenberg Self-esteem scale was used for measuring self-esteem. Participants in the experimental group received group counseling for eight weeks, one day per week, for an hour per session with a total of 8 sessions.